The emergence of Islamic spa concept - Othman, Rashidi; Abdul Halim, Siti Farah Aliyah; Hashim, Khairusy Syakirin Has-Yun; Hj. Baharuddin, Zainul Mukrim; Mahamod, Lukman Hakim (American Scientific Publishers, 2015)
The onset of having a place for women to rejuvenate and refresh their body, mind and soul after a hectic day at work is amazing. Muslim women nowadays are more open to the idea of operating and visiting spa to get the benefits and advantages offered. However, as the awareness of implementing Islamic teaching as a way of life is increasing, spa operators and entrepreneurs are now taking the challenges to open an Islamic concept spa. The emergence of great numbers of Muslimah spa in Malaysia attracts the attention of the researcher to propose the elements that considered following the Shariah law and can be implemented in the present and in the future. There is not enough study about Islamic spa as spa and wellness services is a new scope to be focused in Muslim friendly hospitality services. This paper is an attempt to get the attention of spa operators and organisation to participate in this project and produce reliable resources in promoting Muslim friendly spa in the future